Answer:
The answer is 7.
Step-by-step explanation:
You have to substitute the value of x into the function :
![f(x) = \sqrt{x - 8} + 3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Csqrt%7Bx%20-%208%7D%20%20%2B%203)
![f(24) = \sqrt{24 - 8} + 3](https://tex.z-dn.net/?f=f%2824%29%20%3D%20%20%5Csqrt%7B24%20-%208%7D%20%20%2B%203)
![f(24) = \sqrt{16} + 3](https://tex.z-dn.net/?f=f%2824%29%20%3D%20%20%5Csqrt%7B16%7D%20%20%2B%203)
![f(24) = 4 + 3](https://tex.z-dn.net/?f=f%2824%29%20%3D%204%20%2B%203)
![f(24) = 7](https://tex.z-dn.net/?f=f%2824%29%20%3D%207)
Answer:
1
Step-by-step explanation:
Use PEMDAS to solve the equation, and you will get the answer 1 for x
The answer is: [D]: " 2.6 " .
_____________________________________________________
Given: a = - 2.6 ; What is the value of "-a "?
_____________________________________________________
So, what is the value of " - (-2.6)" ?
_____________________________________________________
The opposite of a negative is a positive;
so, " - (-2.6) = 2.6 " ; which is: "Answer choice: [D] " .
_____________________________________________________
(-1.7, -4.9)
to reflect across the x-axis multiply the x-value by negative 1